2022
DOI: 10.3389/fbioe.2022.945639
|View full text |Cite
|
Sign up to set email alerts
|

Tendon mechanical properties are enhanced via recombinant lysyl oxidase treatment

Abstract: Tendon mechanical properties are significantly compromised in adult tendon injuries, tendon-related birth defects, and connective tissue disorders. Unfortunately, there currently is no effective treatment to restore native tendon mechanical properties after postnatal tendon injury or abnormal fetal development. Approaches to promote crosslinking of extracellular matrix components in tendon have been proposed to enhance insufficient mechanical properties of fibrotic tendon after healing. However, these crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(51 citation statements)
references
References 66 publications
10
40
0
Order By: Relevance
“…Aside from temporal differences in response, collectively we found that endogenous LOXL2 increased mechanical properties without significant effects on DNA concentration, collagen concentration, or collagen organization. This matches many previous studies that have found similar results with endogenous application of 150 ng/ml LOXL2 or greater having no effect on cell viability, cell proliferation, collagen concentration, or collagen organization [24,39,41,45,54]. In this study, while addition of LOXL2 at 2 and 4 weeks did not restrict further cellular development of hierarchical fibers later in culture, we did observe a slight increase in distinct fiber and fascicle organization and a significant decrease in fibril diameter for all LOXL2 treated constructs at 6 and 7 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Aside from temporal differences in response, collectively we found that endogenous LOXL2 increased mechanical properties without significant effects on DNA concentration, collagen concentration, or collagen organization. This matches many previous studies that have found similar results with endogenous application of 150 ng/ml LOXL2 or greater having no effect on cell viability, cell proliferation, collagen concentration, or collagen organization [24,39,41,45,54]. In this study, while addition of LOXL2 at 2 and 4 weeks did not restrict further cellular development of hierarchical fibers later in culture, we did observe a slight increase in distinct fiber and fascicle organization and a significant decrease in fibril diameter for all LOXL2 treated constructs at 6 and 7 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…This pattern of LOX expression closely mirrors previously reported results in developing chick calcaneal tendons, where LOX expression, LOX activity, and PYD accumulation increased temporally throughout development, with more dramatic increases at later stages of development [34,36]. Further, this same group has recently demonstrated that treatment with recombinant LOX at different developmental stages results in increased mechanics, with the biggest effect on mechanics occurring with earlier application when endogenous LOX activity is not as high [54]. Specifically, LOX activity and expression is low at Hamburger-Hamilton stage (HH) HH40 and then significantly increases by HH43 [36], similar to what we observe between 4 and 6 weeks of control constructs.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations